Emerging evidence for a mechanistic link between low-frequency oscillation of ventricular repolarization measured from the electrocardiogram T-wave vector and arrhythmia. Issue 9 (20th April 2021) - Taggart, Peter; Pueyo, Esther; Duijvenboden, Stefan van; Porter, Bradley; Bishop, Martin; Sampedro-Puente, David A; Orini, M; Hanson, B; Rinaldi, Christopher A; Gill, Jaswinder S; Lambiase, Pier
Abstract: Strong recent clinical evidence links the presence of prominent oscillations of ventricular repolarization in the low-frequency range (0.04–0.15 Hz) to the incidence of ventricular arrhythmia and sudden death in post-MI patients and patients with ischaemic and non-ischaemic cardiomyopathy. It has been proposed that these oscillations reflect oscillations of ventricular action potential duration at the sympathetic nerve frequency. Here we review emerging evidence to support that contention and provide insight into possible underlying mechanisms for this association.